Capillary Skimming of Floating Microplastics via a Water‐Bridged Ratchet - Seohyun Cho; Sang Jin Park; Young Jin Lee; You Jun Lee; Young A Lee; Ho‐Young Kim; Seong Jin Kim; Seok Chung; Myoung‐Woon Moon (Advanced Science)
Abstract Floating microplastics (MPs) have recently become a major concern in marine pollution; however, current filter‐based technology is hardly effective for directly removing such MPs from the water surface because of specific mesh size and clogging issues. This paper introduces a new skimming concept for removing floating MPs utilizing capillary force mediated by the elevation of a hydrophilic ratchet at the air−water interface. MPs floating near the ratchet surface are spontaneously forced toward the ratchet with a concave water meniscus, driven by the Cheerios effect. The MPs can then be skimmed and temporarily held by the deforming concave water meniscus as the ratchet rises. Here, it is found that the stability of the water bridge plays a crucial role in skimming success because it provides capillary adhesion between the MP and the ratchet. The proposed capillary skimming method is observed to be effective across nearly all types of floating MPs, ranging in size from 1 to 4 mm, and with densities varying from 0.02 to 0.97 g cm−3, which is also demonstrated by a prototype of marine robot cleaner.